2020
DOI: 10.1051/0004-6361/201936625
|View full text |Cite
|
Sign up to set email alerts
|

Edge collapse and subsequent longitudinal accretion in filament S242

Abstract: Filament S242 is 25 pc long with massive clumps and YSO clusters concentrated in its end regions; it is considered a good example of edge collapse. We mapped this filament in the 12CO(1–0) and 13CO(1–0) lines. A large-scale velocity gradient along filament S242 has been detected; the relative velocity between the two end-clumps is ~3 km s−1, indicating an approaching motion between them. These signatures are consistent with the filament S242 being formed through the collapse of a single elongated entity, where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Elongated filamentary structures produced by gravitational collapse tend to accumulate mass near their ends by means of the so-called edge collapse. Yuan et al (2020) found that the structure of the 25-pc long filament S228 matches the edge collapse predictions. This mechanism can create two adjacent star clusters or groups of stars of comparable masses.…”
Section: Sequential Disk Instability (Di+di)supporting
confidence: 52%
“…Elongated filamentary structures produced by gravitational collapse tend to accumulate mass near their ends by means of the so-called edge collapse. Yuan et al (2020) found that the structure of the 25-pc long filament S228 matches the edge collapse predictions. This mechanism can create two adjacent star clusters or groups of stars of comparable masses.…”
Section: Sequential Disk Instability (Di+di)supporting
confidence: 52%
“…Elongated filamentary structures produced by gravitational collapse tend to accumulate mass near their ends by means of the so-called edge collapse. Yuan et al [51] found that the structure of the 25-pc long filament S228 matches the edge collapse predictions. This mechanism can create two adjacent star clusters or groups of stars of comparable masses.…”
Section: Core Fragmentation and Capture (Cf+cf Di+cf)mentioning
confidence: 75%
“…Ragan et al 2012;Dirienzo et al 2015;Wang et al 2016). They are observed to have multiple substructures and velocity components, which should considerably facilitate the mass aggre-the converging motion, the filaments could also have longitudinal collapse to generate dense clumps and cores at two ends, as shown in both theoretical (Clarke & Whitworth 2015) and observational (Dewangan et al 2019;Yuan et al 2020) works.…”
Section: Introductionmentioning
confidence: 92%